THE EFFECTIVENESS OF ACTIVE DEBATE METHOD IN IMPROVING THE SPEAKING ABILITY OF CLASS V STUDENTS OF STATE 10 PRIMARY SCHOOL SAOTENGAH SINJAI DISTRICT - Rina Harlina; Rahma Ashari Hamzah; Supriadi (Media Inovasi Pendidikan dan Publikasi, 2024)
This research aims to determine the effectiveness of the active debate method in improving the speaking skills of fifth grade students at SD Negeri 10 Saotengah, Sinjai Regency. The population of this research was all students at SD Negeri 10 Saotengah, totaling 73 students. Sampling in this study was carried out using a one group pre test-post test design technique, so the sample in this study was class V students of SD Negeri 10 Saotengah, Sinjai Regency with a total of 15 students consisting of 8 boys and 7 girls. Data collection uses observation sheets, rubrics, tests and documentation. Instrument testing uses validity and reliability. The data analysis technique uses descriptive inferential statistical analysis, namely the normality test, homogeneity test and hypothesis test in the form of a linearity test. From the results of this research, it can be concluded that the use of the debate method can improve the speaking skills of class V students at SD Negeri 10 Saotengah, Sinjai Regency. This is based on the results of research conducted that the data on the comparison of the Pretest and Posttest for the Pros and Cons groups showed a significant influence after using the debate method, with an average pretest score of 65.2 and an average posttest score of 76.9. So this means that Ho and Ha are accepted through several tests, first the validity test, the reliability test, then the normality test and the momogeneity test. Thus, it can be concluded that the use of the debate method is effective in improving students' speaking skills at SD Negeri 10 Saotengah, Sinjai Regency.